Gluco-friendly rice consumption: Balancing the palate with the pancreas - Kalra, Sanjay; N. Mbaye , Maïmouna; Ahomagnon, Sédrick; Teelucksingh, Joel; Selim, Shahjada; Joshi, Shilpa; Nabiswa, Hilda (Journal of the Pakistan Medical Association, 2023)
ice, or Oryza sativa/ Oryza glaberrima is the largest sources of carbohydrates, and calories, for mankind. It is the staple food across many countries of America, Africa and Asia. Hence, we need gluco-friendly ways of incorporating rice-based menus into the cuisine of persons living with diabetes. This multinational article discusses this challenge, and highlights the importance of informed and shared decision making with persons living with diabetes. Keywords: Diabetes, glycaemic index, medical nutritional therapy, Oryza sativa, obesity, person-centered care, rice, type 1 diabetes, type 2 diabetes.